أهمية التدقيق المالي في مكافحة التهرب الضريبي دراسة حالة مديرية الضرائب لولاية سوق أهراس - زيراوي روميسة; إيمان شايب (My University, 2022)
This study aims to know the effective contribution of financial auditing to reducing tax evasion, as this topic is considered a sensitive topic due to its effects on the national economy, especially within the applicable declaration system, and it is known that tax was and still is the largest financial resource The state relies on it to formulate and implement its development policy, but it also constitutes an obstacle for many citizens in light of their lack of tax awareness, which led to the emergence of the so-called tax evasion, which is considered a dangerous and growing scourge that extends its roots based on social, economic, as well as political conditions. Therefore, we find that financial audit plays an effective role in combating tax evasion as a preventive and punitive method at the same time, in which the tax administration relies on several means and techniques to confront this phenomenon with the aim of establishing control over the statements made by taxpayers and verifying their validity, and reaching the goal of simplifying Facilitating the tax system for the taxpayers and making them aware of the importance and benefit that accrues to them and the public treasury on the one hand, and the protection of the national economy on the other. ...................................................... تهدف هذه الد راسة إلى معرفة المساهمة الفعالة للتدقيق المالي في الحد من التهرب الضريبي، حيث يعتبر هذا الموضوع موضوعا حساسا لما ينطوي عليه من تأثيرات على الاقتصاد الوطني، خاصة ضمن نظام التصريحات المعمول بها، كما أ ن و ومن المعروف أ ن الضريبة كانت ولا تزال بمثابة أكبر مورد مالي تعتمد عليها الدولة في رسم وتنفيذ سياستها التنموية، إلا أ ن عاق أمام الكثير من المواطن الوعي الضريبي لديهم، ما أدى إلى ما يسمى بالتهرب الضريبي ا لذي يعتبر آفة خطيرة متنامية تمتد جذورها استنادا للظروف الاجتماعية والاقتصادية وكذا السياسية منها. لذا نجد أ ن للتدقيق الدالي دورا فعالا في مكافحة التهرب الضريبي باعتباره أسلوب وقائي وعالي في آن واحد، حيث تعتمد فيه الإدارة الجبائية على عدة للوقوف في هذه الظاهرة بهدف وضع رقابة على التصريحات ا لتي يادمها المكلفون بالضريبة والتأكد من صحتها، والوصول إلى هدف تبسيط وتسهي النظام الضريبي على الخاضعين وتحسيسهم بالأهمية والنفع ا لذي يعود عليهم وعلى الخزينة العمومية من جهة وحماية الاقتصاد الوطني من جهة أخرى.